Photophysical Switching between Aggregation‐Induced Phosphorescence and Dual‐State Emission by Isomeric Substitution. Issue 17 (27th February 2020) - Xi, Wenbin; Yu, Junru; Wei, Mengru; Qiu, Qianqian; Xu, Pengfei; Qian, Zhaosheng; Feng, Hui
Abstract: It is attractive but highly challenging to achieve controllable regulation of photophysical properties of pure organic luminogens, due to distinct work mechanisms and molecular structures. Here, a strategy to regulate in a controllable way the emission behavior of luminogens is reported, according to which long‐lived aggregation‐induced emission (AIE) can be switched to short‐lived dual‐state emission (DSE) by an isomer‐based substitution reaction. Three luminogens with sharply different photophysical behaviors, including aggregation‐induced phosphorescence and dual‐state fluorescence emission, were obtained through a substitution reaction with three isomers. Freely rotating structures are attributed to aggregation‐induced phosphorescence behavior, whereas twisted rigidification of the molecule greatly contributes to its dual‐state emission phenomenon. This work contributes to the controlled regulation of photophysical behaviors through simple reactions and provides a solid evidence to support the key role of the prohibition of intramolecular rotation in aggregation‐induced emission process and molecular design of dual‐state emitters. Abstract : Switching : A strategy to regulate in a controllable way the emission behavior of luminogens is reported, according to which long‐lived aggregation‐induced emission (AIE) can be switched to short‐lived dual‐state emission (DSE) by an isomer‐based substitution reaction.